Biogeographic and palaeoclimatic relationships of the Middle Pliocene ichthyofauna of the Samoggia Torrent (Bologna, Italy) - Landini, Walter (2010)
New Middle Pliocene ichthyofauna (2.4-2.2 Ma) from central-eastern Italy (Samoggia Torrent, Bologna) are described. These ichthyolites were found in a rather thin laminated layer that was deposited after the 2.4 Ma climatic crisis. The origin of this deposit, in which 31 taxa have been classified, is to be related to anoxic events on a regional and, probably, supraregional scale. This ichthyofaunistic association, which consists of living genera, is characterized by a clearcut predominance of mesopelagic species. The palaeoclimatic characters of these ichthyofauna indicate subtropical-type waters, while from a palaeobiogeographic point of view there is a close relationship with the present-day Atlantic-Mediterranean bioprovince. The Samoggia deposit has yielded six taxa that are absent or only occasionally present in the Mediterranean: one of these, Spratelloides gracilis, is exclusive of the Indo-Pacific bioprovince.